Use of Mulch, Fertilizer and Large Stock in Planting Clay Sites - Mcquilkin, W. E. (Indian Forester, 1946)
The experiment reported in this paper shows that mulching, because of its effect in reducing front heaving, is essential in fall planting on bare clay sites, as is also the use of large, high-grade stock. Fertilizer markedly increased the growth of black locust but was somewhat injurious to red pine. With both species fertilizer reduced the severity of frost heaving.